2014
DOI: 10.1366/13-07383
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Breakdown Spectroscopy (LIBS) of a High-Pressure CO2–Water Mixture: Application to Carbon Sequestration

Abstract: Geologic carbon storage in deep saline aquifers is considered a feasible and possible approach of mitigating the problem of increasing greenhouse gas emissions. However, there are latent risks in which carbon dioxide (CO2) could migrate from the deep saline formations to shallower aquifers. In the event of a significant CO2 leakage to an underground source of drinking water, CO2 will dissolve in the water, thereby increasing its acidity, which could potentially enhance the solubility of various aquifer constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…It was found that DP-LIBS emission is inversely proportional to the pressure of the liquid, and the maximum emission can be obtained when the interpulse delay is set in such a way that the second laser pulse hits the vapor bubble generated by the first pulse when it has the largest diameter. Recent carbonsequestration studies assess the possibility of using LIBS for monitoring purposes in deep saline aquifers, which requires measurements in a high-pressure water-CO 2 mixture [219,220]. It was found that elemental emissions in the liquid were not significantly affected by the presence of dissolved of CO 2 , and thus LIBS was regarded as a viable tool for this monitoring task.…”
Section: Applications Under Extreme Conditionsmentioning
confidence: 99%
“…It was found that DP-LIBS emission is inversely proportional to the pressure of the liquid, and the maximum emission can be obtained when the interpulse delay is set in such a way that the second laser pulse hits the vapor bubble generated by the first pulse when it has the largest diameter. Recent carbonsequestration studies assess the possibility of using LIBS for monitoring purposes in deep saline aquifers, which requires measurements in a high-pressure water-CO 2 mixture [219,220]. It was found that elemental emissions in the liquid were not significantly affected by the presence of dissolved of CO 2 , and thus LIBS was regarded as a viable tool for this monitoring task.…”
Section: Applications Under Extreme Conditionsmentioning
confidence: 99%
“…Previous work in our and other laboratories has shown that underwater LIBS can successfully be used for the elemental analysis of aqueous solutions with and without a saline sample matrix. These studies focus on measurements at high pressure 4,1420 , as well as at atmospheric pressure 21–27 conditions. The underwater LIBS technique relies on focusing a high peak power pulsed laser into a liquid sample to generate a plasma.…”
Section: Introductionmentioning
confidence: 99%
“…A LIBS device (ChemiCam module) was installed in a ROV and deep sea in situ tests were done to obtain the chemical composition of seawater and perform a geochemical test of mineral deposits for the first time [ 12 ]. The improvement of this method is an ongoing topic of research [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. One way to improve this method is to use double pulse and multi pulse laser breakdowns [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%